A state‐of‐the‐art review on creep damage mechanics of rocks. Issue 3 (3rd January 2022) - Zhou, Xiaoping; Pan, Xiaokang; Berto, Filippo
Abstract: In many major rock projects, services have spanned decades or even hundreds of years. For engineering design, it is necessary not only to ensure the safety of personnel during construction but also to ensure the safety of long‐term use and operation in the future. Therefore, it is indispensable to study the creep damage mechanical properties of rocks before the construction of the project. For a long time, rock creep has been an important reason for large deformation and even instability in building foundations, underground tunnels, and slopes. Moreover, the surrounding rock generally exhibits obvious creep damage characteristics under an environment of high stress, high temperature, and high water‐pressure. Under certain geological conditions, this creep damage behavior is extremely prominent. Therefore, the study of rock creep damage mechanics is very important. This paper reviews the advancement of rock creep damage mechanics from the aspects of mechanisms, research methods, constitutive models, and so forth. Rock creep is a process of interaction between structural damage and the hardening effect. The structural damage and hardening effect are opposite to each other, but they exist in the same physical process. The creep research method introduces mainly the research objects, influencing factors, monitoring methods, and experimental methods. Creep constitutive models introduce mainly empirical models, linear element combination models, nonlinear combination models, and other nonlinear models based on new theory. Finally, based on the current research progress, several important research directions in rock creep damage mechanics are pointed out. Highlights: The rock creep and damage mechanism is analyzed. The creep experimental methods are summarized. The research progress of the creep constitutive models is discussed. Several important research directions in rock creep mechanics are pointed out.